Physical Activity Among Obese And Non-Obese School-Aged Children in An Elementary School in Makassar - Kadek Ayu Erika; Syahrul Syahrul; Ilkafah Ilkafah; Arnis Puspitha (Journal of Health Science and Prevention, 2019)
The Prevalence of obesity among children in the urban areas is increasing due to less physical activity, high consumption of fast-food, and more time spent on using the gadget. This study aimed to identify physical activity among obese and non-obese children. This descriptive study involved 322 obese and non-obese students from 4th to 6th grade in an elementary school in Makassar. Physical Activity Questionnaire for Older Children (PAQ-C) was used to measure children’s physical activity, while the anthropometrical parameter was measured using a standardized instrument. Children’s body mass index for age z-score (BAZ) was used to classify their nutritional status based on the criteria of Growth Reference for Children from 5 to 19 years old from World Health Organization. Cross-tabulation was used in analyzing the data. Obese and non-obese children in this study were found 53 (16,0%) and 279 (84,0%), respectively. A hundred percent of obese children have low physical activity, while non-obese children have better physical activity. In conclusion, elementary school students in this study have low physical activity, particularly among obese children. Children are rarely spent on their time to do physical activity. There is a need to promote appropriate physical activity among children to prevent and treat obesity among children. Health professionals could provide health education and counseling to children, family and/or schools to manage physical activity among children.